2005
DOI: 10.1002/jmor.10375
|View full text |Cite
|
Sign up to set email alerts
|

Clonal domains in postlarvalPlatynereis dumerilii (Annelida: Polychaeta)

Abstract: Following an enzymatic procedure for softening the egg envelope, blastomeres in the embryo of the polychaete Platynereis dumerilii were injected with TRITC-dextran. Injection was successful in the following blastomeres: AB, CD, A, B, C, D, 1a-1d, 1A-1D, 4d, and 4d(1). The distribution of fluorescent label was recorded by confocal laser scanning microscopy of young, three-segmented worms after 3 or 4 days of development, in some cases also in 1-day-old trochophore larvae. Results were documented by single optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 36 publications
3
136
1
Order By: Relevance
“…This has not been resolved unambiguously in Platynereis to date. Lineage tracings of blastomere fates with diI in cleavage-stage embryos of Platynereis have been carried out up to three days of development (Ackermann et al, 2005). Injection of the 4d blastomere, which belongs to a homologous lineage to the leech DM blastomere labels the whole trunk mesoderm of the larva but more heavily labels a small group of cells located internally just in front of the forming pygidium.…”
Section: A New Comprehensive Definition Of Annelid Teloblastsmentioning
confidence: 99%
“…This has not been resolved unambiguously in Platynereis to date. Lineage tracings of blastomere fates with diI in cleavage-stage embryos of Platynereis have been carried out up to three days of development (Ackermann et al, 2005). Injection of the 4d blastomere, which belongs to a homologous lineage to the leech DM blastomere labels the whole trunk mesoderm of the larva but more heavily labels a small group of cells located internally just in front of the forming pygidium.…”
Section: A New Comprehensive Definition Of Annelid Teloblastsmentioning
confidence: 99%
“…A second technique, called 4D microscopy, utilizes time-lapse imaging to follow individual cells using a semi-automated cell tracking system . This methodology requires optically clear embryos and gives detailed cell division information, but there is limited or no of the fate map were inferred by subtractive logic (Ackermann et al, 2005). A second Platynereis study utilized 4D microscopy to examine cleavage patterns (Fischer and Arendt, 2013).…”
Section: Spiralian Fate Mapsmentioning
confidence: 99%
“…In polychaetes, there are only four modern cell lineage or fate mapping studies published to date, including two studies each for Capitella teleta and Platynereis dumerilii (Ackermann et al, 2005, Fischer and. In one Platynereis study, identified blastomeres were microinjected for a limited set of blastomeres (1 st quartet micromeres, 1 st quartet macromeres, 2d 112 , 4d and 4d 1 ), and several features B C A Spiralian development in polychaetes 461 (Eisig, 1899), although his results were received with skepticism by his contemporaries (Nelson, 1904, Treadwell, 1901.…”
Section: Spiralian Fate Mapsmentioning
confidence: 99%
“…Yet, in mollusks, the mesodermal bands have generally been described as mostly less extensive and rather short lived, especially when compared to the situation in annelids (Korschelt and Heider, 1936; Raven, 1966; Fioroni, 1971, 1992; Wanninger and Wollesen, 2015). In the worm‐shaped solenogasters, however, the mesodermal bands seem to acquire larger dimensions and persist for a considerable period of time–a condition, which is more similar to other spiralians, especially annelids (e.g., Mead, 1897; Schmidt, 1925; Okada, 1940; Anderson, 1959, 1966, 1973; Goto et al., ’99; Ackermann et al., 2005; Seaver et al., 2005; Dill et al., 2007; Woodruff et al., 2007; Fischer and Arendt, 2013). Furthermore, the situation we observed is in agreement with classical descriptions on mesoderm formation and differentiation of solenogasters and polyplacophorans (Pruvot, 1890, 1892; Heath, 1899; Naef, 1924; Hammarsten and Runnström, 1925; Baba, 1938; Thompson, 1960; Salvini‐Plawen and Bartolomaeus, 1995) but is demonstrated here for the first time over the entire course of development using state‐of‐the‐art techniques.…”
Section: Discussionmentioning
confidence: 99%